Treatment of lateral canthal rhytides with a medium depth chemical peel with or without pretreatment with onabotulinum toxin type A: a randomized control trial - Rebecca Tung, MD; Anne Marie Mahoney, MD; Karlee Novice, MD; Loebat Kamalpour, MD; Meghan Dubina, MD; Meredith Hancock, MD; Cindy Krol, BS (Wolters Kluwer, 2016)
Background: Combination therapies used to treat the photoaged skin have become more popular as studies demonstrate greater efficacy and improved clinical outcomes compared to single treatment modalities. Objectives: To evaluate the safety and effectiveness of treating the lateral canthal rhytide complex with a Jessner's and 35% TCA peel with and without pretreatment with BTX-A. Methods: Twenty-six subjects with Fitzpatrick skin types I -III were randomized to receive treatment of their lateral canthal rhytide complex with a Jessner's and 35% TCA peel with or without pretreatment with BTX-A. A single blinded dermatologist assigned a lateral canthal wrinkle score of subjects' at baseline and week 8-10. Results: Comparison between the two treatment groups demonstrated that the group receiving combination treatment had significantly greater improvement in wrinkle reduction as compared to the group only receiving the chemical peel (P =0.002). In addition, there was no significant association between skin type and treatment groups (P = 0.11). Conclusions: These findings suggest that treating the lateral canthal rhytide complex with a combination of BTX-A followed by Jessner's and 35% TCA peel is more effective than chemical peel alone. These results are independent of skin type and demonstrate an additional treatment strategy for lateral canthal rhytides.